Efektivitas Intervensi Relaksasi Imaginasi Terbimbing Terhadap Penurunan Kecemasan dan Nyeri pada Pasien Paliatif - Fitri Wulandari; Elly Nurachmah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Anxiety and pain are problems that often occur in patients with chronic diseases. One of the goals of palliative care is to relieve physical symptoms that are felt and other things that make physical and psychological stress. Alternative and complementary medicine approaches can be an option for palliative patients and families where conventional treatment has not been able to reduce or relieve the symptoms they feel. : Complementary therapies can be provided to patients receiving palliative care, to integrate a multi-professional palliative approach. The development of effective intervention selection is very important for the success of its treatment. Guided imagination is one of the complementary therapies that can provide physical and psychological benefits. Therefore, the purpose of this literature study was to determine the effectiveness of guided imaginary relaxation in reducing anxiety and pain levels in palliative patients. Methods: This literature review was compiled using the databases of EBSCOHost, Clinical Key Nursing and Sage Journal. Four articles were obtained that were following the randomized control randomization research method. Results: After further analysis of the four articles, guided imagination techniques accompanied by music were more effective in reducing pain and anxiety and could increase feelings of well-being when combined with other complementary therapies such as progressive muscle relaxation and hand massage. Conclusion: Within the various complementary therapies available, each aims to develop a holistic balance for the individual by enhancing physical, psychological, and spiritual well-being. Guided imagery helps patients by diverting their attention from the disease, its associated side effects, negative thoughts, and emotions, and focusing instead on pleasant things.